Blocking Neurogenic Inflammation for the Treatment of Acute Disorders of the Central Nervous System. (29th May 2013) - Lewis, Kate Marie; Turner, Renée Jade; Vink, Robert
Abstract : Classical inflammation is a well-characterized secondary response to many acute disorders of the central nervous system. However, in recent years, the role of neurogenic inflammation in the pathogenesis of neurological diseases has gained increasing attention, with a particular focus on its effects on modulation of the blood-brain barrier BBB. The neuropeptide substance P has been shown to increase blood-brain barrier permeability following acute injury to the brain and is associated with marked cerebral edema. Its release has also been shown to modulate classical inflammation. Accordingly, blocking substance P NK1 receptors may provide a novel alternative treatment to ameliorate the deleterious effects of neurogenic inflammation in the central nervous system. The purpose of this paper is to provide an overview of the role of substance P and neurogenic inflammation in acute injury to the central nervous system following traumatic brain injury, spinal cord injury, stroke, and meningitis.